2022
DOI: 10.1038/s41598-022-13023-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting neural deficits in sensorineural hearing loss from word recognition scores

Abstract: The current gold standard of clinical hearing assessment includes a pure-tone audiogram combined with a word recognition task. This retrospective study tests the hypothesis that deficits in word recognition that cannot be explained by loss in audibility or cognition may reflect underlying cochlear nerve degeneration (CND). We collected the audiological data of nearly 96,000 ears from patients with normal hearing, conductive hearing loss (CHL) and a variety of sensorineural etiologies including (1) age-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 85 publications
2
18
0
Order By: Relevance
“…Noise-induced temporary threshold shift (TTS) in the absence of permanent threshold shift (PTS) can be accompanied by permanent damage to the synaptic connections between the cochlear inner hair cells (IHCs) and auditory nerve (AN) dendrites (cochlear synaptopathy) (see Kujawa and Liberman, 2009 ). A variety of data suggest that cochlear synaptopathy — inferred from evoked potential measurements — is correlated with hearing-in-noise difficulties in patients/participants who exhibit clinically normal-hearing sensitivity (thresholds 0.25–8 kHz ≤ 25 dB HL) ( Grant et al, 2020 , 2022 ; Mepani et al, 2021 ; Wu et al, 2021 ). Hazardous noise exposure is better known for compromising outer hair cell (OHC) integrity, and is associated with decreased distortion product otoacoustic emission (DPOAE) amplitude ( Poling et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Noise-induced temporary threshold shift (TTS) in the absence of permanent threshold shift (PTS) can be accompanied by permanent damage to the synaptic connections between the cochlear inner hair cells (IHCs) and auditory nerve (AN) dendrites (cochlear synaptopathy) (see Kujawa and Liberman, 2009 ). A variety of data suggest that cochlear synaptopathy — inferred from evoked potential measurements — is correlated with hearing-in-noise difficulties in patients/participants who exhibit clinically normal-hearing sensitivity (thresholds 0.25–8 kHz ≤ 25 dB HL) ( Grant et al, 2020 , 2022 ; Mepani et al, 2021 ; Wu et al, 2021 ). Hazardous noise exposure is better known for compromising outer hair cell (OHC) integrity, and is associated with decreased distortion product otoacoustic emission (DPOAE) amplitude ( Poling et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, word recognition scores (WRSs) in the best and worse hearing ear were also collected. WRS was measured using recorded W-22 lists in quiet with consistent logic for presentation level (21). Lastly, the type of hearing loss (normal, sensorineural, mixed, or conductive) in the best and worse hearing ear was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, animal studies have shown that the audiogram is not a valid metric for determining the extent of damage within the cochlea. Specifically, damage to the outer and/or inner hair cells must be used cautiously to diagnose pathology as the loss of neural connections within the ear (i.e., synaptopathy) can reach 80% without significantly impacting audiometric thresholds 28–31 …”
Section: Diagnosis First Treatment Secondmentioning
confidence: 99%
“…Word Recognition Scores (WRSs): Traditional WRSs are not a rigorous metric of hearing and/or listening capabilities. Indeed, 60% or more neural damage must be present before its contribution is witnessed via traditional WRSs in quiet 28 …”
Section: Diagnosis First Treatment Secondmentioning
confidence: 99%